(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Learning a language is an exploitation of the capacitiesof the mind to make sense of the environment. The private process takes placein the public contexts of the classroom. This internal process of languagelearning takes place as a result of the external interaction between the twoparticipants- the teacher and the learner and the internal interaction betweenthe learner’s cognition and learning material. Interaction is a process in whichthe people or things have a reciprocal effect upon each other through theiractions Interaction may be between the teacher and the student, student and thestudent, teacher and the group and the student’s schema or previous knowledgerelated to content and the new learning material. Effective classroominteiaction leads to effective learning Whatever pedagogic approach is taken itis the interaction in the classroom that mediates between teaching andlearning. The teacher must engage in the sort of interaction, which will enablecommunication to take place and learning to occur. Flanders (1970) is of theopinion that "skills of interaction muse be developed for developing one’sown teaching behaviour and to improve the learning of the learner"(p.4).Thomas (1987) suggests, "The factors, which enter into interaction, shouldbe subjected to careful and critical examination and their implications forpedagogic practice explored in the context of actual classrooms" (p 6)